Farmers’ Perception of Etawah Grade Goat Productivity Based on the Hair Color Differences - Budisatria, I Gede Suparta; Panjono, Panjono; Maharani, Dyah (Faculty of Animal Science, Universitas Gadjah Mada Yogyakarta, Indonesia, 2015, 2015)
In recent year, there is a tendency that farmers prefer to keep Etawah grade goat with black head color instead of brown or mixed colors, therefore the study was conducted to identify the farmers’ perception in regard with the effect of hair color differences on the productivity of Etawah grade goats. Sixty farmers were interviewed deeply on their perception using a semi structured questionnaire; farmers were selected randomly from two districts, Sleman and Kulonprogo, which have been known as the centre of Etawah grade goats in Yogyakarta Province. The interviews were conducted for three months using “door to door” method, including farmers characteristics, the reason to select different hair color, mating systems, the kid produced, the price of goats based on different hair color, and the effect of different hair color on feed intake and productivity. Data was tabulated and analyzed descriptively. The result indicated that the majority reason of farmers kept the specific hair color of goats due to the expensive prices (40.00%), excellence exterior characteristics (38.33%), and a few farmers stated that they select different hair color because the goats had high performance, i.e. high milk production (13.33%) and rapid growth rate (8.33%). Farmers mostly (85.00%) mated their Etawah grade doe using a buck which has the same color with the doe, while the rest (15.0%) mated their doe sometimes with different hair color of buck. In addition, farmers also believed that the kids will have the same colors with their parents (76.67%), however, some of 23.33% farmers had experience that mating between doe and buck which has the same color will not automatically produce kid with the same hair color. The difference hair color betwen the kids and their parents was found relatively small, less than 25%. There was a significant differences of price between black head color hair and brown or mixed color acoding to more than 86% farmers, the different price approximately IDR 399,000,00, The different price of goats seem to be based on their excellent exterior characteristic (66.67%) and high demand (21.67%) rather than high milk production (6.67%) and rapid growth rate (5.00%). Majority of farmers did not agree (68.33%) and only a few farmers (21.67%) stated that productivity was related to diferent hair color, while 10% of the farmers did not know whether it will affect the productivity or not. It can be concluded that expensive prices and exterior characteristics was the main reason for the farmer to select and keep Etawah grade goats. Kids produced will not automatically have similar color with their parent. Farmers believed that color differences will not have impact on the productivity of goats, however goats with black head color remain have the most expensive price for excellent exterior performance reason.